2013
DOI: 10.1016/j.ajo.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Focal Choroidal Excavation in Eyes With Central Serous Chorioretinopathy

Abstract: Focal choroidal excavations were present in 7.8% of eyes with CSC. In these eyes, focal choroidal excavations may have formed from RPE retraction caused by focal scarring of choroidal connective tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
121
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(135 citation statements)
references
References 37 publications
10
121
3
1
Order By: Relevance
“…[3][4][5][6][7] In our study, the prevalence of FCE in CSC patients was found to be 6.0%, which was slightly lower compared with the prevalence of 7.8% reported by Ellabban et al 4 in 116 eyes with CSC. However, our rate was higher than the prevalence of 2.8% reported by Suzuki et al 6 in another Japanese study of 248 eyes with CSC.…”
Section: Discussioncontrasting
confidence: 46%
See 4 more Smart Citations
“…[3][4][5][6][7] In our study, the prevalence of FCE in CSC patients was found to be 6.0%, which was slightly lower compared with the prevalence of 7.8% reported by Ellabban et al 4 in 116 eyes with CSC. However, our rate was higher than the prevalence of 2.8% reported by Suzuki et al 6 in another Japanese study of 248 eyes with CSC.…”
Section: Discussioncontrasting
confidence: 46%
“…This rate was higher compared with previous studies in which 0-24% of patients had FCE bilaterally. [3][4][5][6][7][8][9] The natural course of FCE remains unclear as most of the published studies were cross-sectional studies. There were only a few studies with longitudinal follow-up data available and the majority of the excavations appeared to remain stable with follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations